Development of Android-Based Pencak Silat Learning Media for High School Students - Pedomanta Keliat; Muhammad Syaleh; Ahmad Al Munawar (Universitas Negeri Medan, 2021)
This research is a development research (RnD) where the stages in its implementation are 4D steps, namely Define, Design, Development and Dessimination. The data collection instrument used observation, interview and closed questionnaire distribution to 30 respondents (high school students). Product testing is carried out through the justification of two experts who are in charge of escorting the product to be produced. Before the product is tested on the respondent, it is very important that consulting activities with these experts maintain the direction and steps taken in accordance with the original objectives. The experts involved in this research activity are one expert in learning pencak silat and one expert in learning media.The data analysis used is descriptive in which expert judgment and respondent's assessment will determine the final product result. This product has been assessed by respondents through questionnaires where the score obtained is 53.11 when converted, the resulting product gets the predicate